A fluorescent nanoprobe based on AIEgen: Visualization of silver ions and sensing applications in cancer cells and S. aureus. (February 2022) - Kim, Na Hee; Kang, Rae Hyung; Verwilst, Peter; Kim, Dokyoung
Abstract: We have developed a fluorescent nanoprobe (AgP-1 ) that can detect silver ions (Ag + ) in biological media. For the first time, a hybridized structure based on AIEgen (tetraphenylethylene; TPE) and 2-(methylthio)aniline (MTA) moiety has been designed, and its unique sensing properties toward silver ions were systematically analyzed. The nanoprobe AgP-1 has an aggregated form with weak fluorescence and showed significant fluorescence enhancement (3.7-fold) upon forming complex with silver ions. AgP-1 has high selectivity, high sensitivity (detection limit 6.6 ppb), a fast response time (fluorescence enhancement within 10 s), and superior biocompatibility. Visualization of silver ions in cancer cells (U87 glioblastoma) and bacteria ( S. aureus ) was also successfully demonstrated. We believe AgP-1 holds a great potential to serve as a practical sensor for silver ions detection in biomedical applications. Graphical abstract: Image 1 Highlights: For the first time, we developed a fluorescent nanoprobe based on AIEgen to detect silver ions. The nanoprobe showed high selectivity, sensitivity, and fast response time. The nanoprobe showed superior biocompatibility for the silver ion with high biocompatibility.